# Solve for y -2/3+5/3=7/5y+2/5y

-23+53=75y+25y
Rewrite the equation as 75y+25y=-23+53.
75y+25y=-23+53
Simplify 75y+25y.
Simplify each term.
Combine 75 and y.
7y5+25y=-23+53
Combine 25 and y.
7y5+2y5=-23+53
7y5+2y5=-23+53
Simplify terms.
Combine the numerators over the common denominator.
7y+2y5=-23+53
9y5=-23+53
9y5=-23+53
9y5=-23+53
Simplify -23+53.
Combine the numerators over the common denominator.
9y5=-2+53
9y5=33
Divide 3 by 3.
9y5=1
9y5=1
Multiply both sides of the equation by 59.
59⋅9y5=59⋅1
Simplify both sides of the equation.
Simplify 59⋅9y5.
Cancel the common factor of 5.
Cancel the common factor.
59⋅9y5=59⋅1
Rewrite the expression.
19⋅(9y)=59⋅1
19⋅(9y)=59⋅1
Cancel the common factor of 9.
Factor 9 out of 9y.
19⋅(9(y))=59⋅1
Cancel the common factor.
19⋅(9y)=59⋅1
Rewrite the expression.
y=59⋅1
y=59⋅1
y=59⋅1
Multiply 59 by 1.
y=59
y=59
The result can be shown in multiple forms.
Exact Form:
y=59
Decimal Form:
y=0.5‾
Solve for y -2/3+5/3=7/5y+2/5y

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top